Injury rates and economic cycles in the Italian manufacturing sector. (18th July 2018) - Farina, E; Giraudo, M; Costa, G; Bena, A
Abstract: Background: There is a procyclical relationship between economic growth and occupational injury rates in the short term. Injury rates rise during periods of economic growth and fall during recessions. Aims: To estimate injury rates for the manufacturing sector in Italy between 1994 and 2012 and their correlation with major macroeconomic factors and to identify a possible change in the trend of injury rates at the beginning of the 2008 economic crisis. Methods: Total and annual serious injury rates were calculated for the national sector. We used a linear autoregressive model to assess the relationship between injury rates and unemployment rate/real GDP growth, and a joint-point regression analysis to analyse changes in injury rates over time. Results: After adjusting for the spontaneous dynamic change in injury rates over time, both total and serious injury rates were negatively associated with unemployment rate, and significantly positively associated with real GDP growth. Manufacturing injury rates dropped after 2008. Conclusions: Manufacturing injury rates are associated with major macroeconomic factors. Workplace injury rates declined between 1994 and 2012. This downward trend was further accelerated after 2008. The changes in workforce composition before and after 2008 partly explain the procyclical relationship between business conditions and injury rates.